Pengaruh Media Animasi terhadap Hasil Belajar Siswa Kelas XI Materi Persebaran Flora Fauna Indonesia dan Dunia di SMAN 1 Batang Anai - Janah, Raudatul; Ernawati, Ernawati (Al-DYAS, 2024)
The use of media in learning is very important in supporting learning activities to achieve learning objectives. Effective use of media can help improve the quality, effectiveness of learning and learning outcomes. The method used in this research is quantitative with the type of experimental research and Quasi Experimental design. The sample in this research was 69 class XI students. The research results show that there is a significant influence on the use of animation media on learning outcomes. Based on the results of calculations using the t-test, a significance level of 5% = 1.99601 is obtained, meaning that t-test is 5.351 > 1.99601 t-table so that Ha is accepted. The average value in the experimental group was also 80.82, which was greater than the average value in the control group of 68.91. And the N-Gain test shows that the average N-Gain Score for the experimental class is 57.3501 or 57.35%, including the "Quite Effective" category. It can be concluded that there is an influence of the use of animation media on learning the distribution of flora and fauna in Indonesia and the world.